The early qadariyya - Judd, Steven C. (The Oxford Handbook of Islamic Theology, 2014)
This article discusses the briefly significant Qadariyya movement during the Umayyad period, with an emphasis on how the movement and its adherents were treated in later sources. The article examines the doctrine of human free will advocated by the Qadariyya, exploring the impetus behind their theological viewpoints and the doctrinal complications that accompanied human free will. It also addresses the debate about the origins of both the doctrine and the movement, and the significance of accusations of Christian roots. The article discusses the views ascribed to prominent Qadari leaders, including Maʿbad al-Juhanī and Ghaylān al-Dimashqī, as well as the systematic persecution of the Qadariyya, led by al-Awzāʿī. It also examines the politicization of the Qadariyya and their entanglement with Yazīd (III) b. al-Walīd’s rebellion during the third fitna. Finally, the article addresses the eclipse of the Qadariyya by the Muʿtazilites.
Keywords: dept.his